Effect of corn flour and storage period on sensory and physiochemical properties of chicken meatball - Al-Mamun, MA; Khan, M; Hashem, MA (Bangladesh Journal of Animal Science, 2018)
The present study was undertaken to evaluate the effect of different levels of corn flour on the quality characteristics of chicken meatball. The meatballs were formulated having 0, 05, 10 and 15% of corn flour. After formulation, samples were preserved at -20˚C for 60 days and analyzed the data at 0, 15, 30 and 60th day, respectively. The products were analyzed for various sensory, proximate, biochemical and physicochemical attributes. The sensory (color, flavor, tenderness, juiciness and overall acceptability), proximate composition- dry matter (DM), ether extract (EE), crude protein (CP) and ash, biochemical parameters- free fatty acid (FFA), peroxide value (PV) and thiobarbituric acid value (TBARS) and physicochemical (raw pH, cooked pH and cooking loss) were analyzed. Data were analyzed in a 4x4 factorial experiment in completely randomized design with replicated three times per cell. Results showed that corn flour inclusion in meatballs have no effect on sensory parameters, but the highest value for all sensory parameters was found at 15th day storage period, (p<0.05). After 15th day, with the increasing of storage period the value for all sensory parameters were decreased (p<0.05). The proximate component’s value were differ with treatment and day interval group (p<0.05). The highest value of raw pH and lowest value of cooking loss were found in 5% corn flour group (p<0.05). The highest value of cooked pH and lowest value of cooking loss were found at 15th day storage period. There were no effect of treatment or day interval on FFA and TBARS. Highest value of PV were found in 0% cornflower group (p<0.05). It may be concluded that 5% corn flour and 15 days storage period is suitable for chicken meat ball. Bang. J. Anim. Sci. 2017. 46 (3): 164-171